Scottish Budget 2023-24: further analysis - Bee Boileau; Kate Ogden; David Phillips; Luke Sibieta; Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2023)
The aim of this report, the IFS's first in-depth analysis of the Scottish Government Budget, is to look at some of the key implications for the coming year, and for the longer term. We do not attempt to cover all of the different services that the Scottish Government is responsible for, or all revenue streams, but instead look at those issues most pertinent to current political and public debates. We therefore focus on the overall funding outlook, income tax revenue performance, local government funding, and the distributional effects of tax and benefit reforms.
Keywords: 330; Education and skills; Government finances and spending; Taxes and benefits; Scottish Budget 2023-24; Devolved government finances; Tax; Benefits; Education; Income taxes; Property taxes; Government spending; Local government finance; Scottish independence